2023
DOI: 10.1158/0008-5472.can-22-2129
|View full text |Cite
|
Sign up to set email alerts
|

SWI/SNF Blockade Disrupts PU.1-Directed Enhancer Programs in Normal Hematopoietic Cells and Acute Myeloid Leukemia

Abstract: In acute myeloid leukemia (AML), SWI/SNF chromatin remodeling complexes sustain leukemic identity by driving high levels of MYC. Previous studies have implicated the hematopoietic transcription factor PU.1 (SPI1) as an important target of SWI/SNF inhibition, but PU.1 is widely regarded to have pioneer-like activity. As a result, many questions have remained regarding the interplay between PU.1 and SWI/SNF in AML as well as normal hematopoiesis. Here we found that PU.1 binds to most of its targets in a SWI/SNF-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 74 publications
5
21
0
Order By: Relevance
“…In addition, AML cell lines display substantial variation in sensitivity to BRG1-targeting gRNAs in DepMap, being a critical dependency in some and neutral in others. This has also been observed in the context of BRG1 inhibitors 17,18 . The sensitivity to BRG1 inhibition has been ascribed to PU.1 (Sp1) 17,18 , however, in DepMap PU.1 is a neutral gene in M07e.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…In addition, AML cell lines display substantial variation in sensitivity to BRG1-targeting gRNAs in DepMap, being a critical dependency in some and neutral in others. This has also been observed in the context of BRG1 inhibitors 17,18 . The sensitivity to BRG1 inhibition has been ascribed to PU.1 (Sp1) 17,18 , however, in DepMap PU.1 is a neutral gene in M07e.…”
Section: Discussionsupporting
confidence: 65%
“…Integration of PRC2 sites in untransformed umbilical cord HSPCs with C/G fusion binding sites in leukemia- like cells identified MYCN as a target, indicating that MYC-family members play a more significant role in C/G AML than previously appreciated. ZBTB16, ZFPM1 and LMO2 are also C/G targets and DepMap dependencies, and may comprise a core regulatory circuit along with GATA-1 and GATA-2 in this subtype of AML as LMO2 does in other AMLs 18 . Single cell transcriptomic analyses of differentiating, untransduced cord blood cells found that many of these genes are already expressed in megakaryocyte progenitors, and that ZBTB16 and ZFPM1 are preferentially expressed in MEPs and GMPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted in 66 hits in THP-1 dCas9 cells and 169 in MOLM-13 dCas9 cells, with 63 of the identified hits shared between the two cell lines (Figs 1A and B,and EV1B,and Dataset EV2). Among the shared hits, there were multiple common essential genes, and several factors previously reported to sustain the proliferation of leukemic cells (e.g., KDM1A, MEN1, PRMT5, and SWI/SNF complex components) (Yokoyama et al, 2004;Caslini et al, 2007;Shi et al, 2013;Cruickshank et al, 2015;Radzisheuskaya et al, 2019;Ravasio et al, 2020;Rago et al, 2022;Chambers et al, 2023). We focused the further investigation on BPTF (Figs 1C and EV1C) since it has not been previously studied in the context of AML.…”
Section: Bptf Is Required For the Proliferation Of Acute Myeloid Leuk...mentioning
confidence: 99%
“…Findings presented demonstrate that treatment with FHD-286 overcame differentiation block and significantly induced in vitro differentiation and loss of viability in AML cell lines and PD AML cells with MLL1r or mtNPM1 similar to those reported earlier (14,15). FHD-286-induced lethality was associated with marked perturbations in chromatin accessibility, inhibition of enhancers, core regulatory circuitry and gene expressions in the AML cells (2,7,16,17). Our findings also demonstrate in vivo efficacy of monotherapy with FHD-286, including depletion of leukemia-initiating AML stem-progenitor cells, reduction of AML burden and significant survival gains in PDX models of AML with MLL1r or mtNPM1 (14,15,18).…”
Section: Introductionmentioning
confidence: 99%